Emotional prototypes, emotional memory usages, and customer satisfaction - Akgun, Ali E.; Keskin, Halit; Alan, Alev Kocak (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2017)
In this study, we investigated the positive and negative emotion concepts in the prototype perspective and then tested them on customer satisfaction. By studying 612 customers in luxury restaurants, we found that two levels of customer emotions (i.e. positive and negative emotions) as a super-ordinate level, 4 positive emotions (i.e. contentment, happiness, love, and pride) and 5 negative emotions (i.e. anger, fear, sadness, shame, and disgust) as a basic level, and 49 specific emotions as a subordinate level are significantly related to customer satisfaction. We also examined the moderating role of emotional memory (EM) usage in the relationship between consumers' emotions and their satisfaction. We found that product (food and beverage)-related EM strengthens and service-related EM usage weakens the relationship between customers' negative emotions and their satisfaction. Interestingly, we found that positive and negative emotions are significantly related to customer satisfaction regardless of experience and store-related EM usage.
Keywords: Consumer emotion; emotional prototype; customer satisfaction; emotional memory; BEHAVIORAL INTENTIONS; CONSUMPTION EMOTION; LUXURY RESTAURANTS; POSITIVE EMOTIONS; EXPERIENCES; QUALITY; IMPACT; MODEL; FOOD; Business & Economics